Predicting psychiatric risk: IgG N-glycosylation traits as biomarkers for mental health - Lv, Yinchun; Chen, Yulin; Li, Xue; Huang, Qiaorong; Lu, Ran; Ye, Junman; Meng, Wentong; Fan, Chuanwen; Mo, Xianming (Frontiers in Psychiatry, 2024)
BackgroundGrowing evidence suggests that chronic inflammation, resulting from intricate immune system interactions, significantly contributes to the onset of psychiatric disorders. Observational studies have identified a link between immunoglobulin G (IgG) N-glycosylation and various psychiatric conditions, but the causality of these associations remains unclear.MethodsGenetic variants for IgG N-glycosylation traits and psychiatric disorders were obtained from published genome-wide association studies. The inverse-variance-weighted (IVW) method, MR-Egger, and weighted median were used to estimate causal effects. The Cochran’s Q test, MR-Egger intercept test, leave-one-out analyses, and MR-PRESSO global test were used for sensitivity analyses.ResultsIn the Psychiatric Genomics Consortium (PGC) database, genetically predicted IGP7 showed a protective role in schizophrenia (SCZ), major depressive disorder (MDD), and bipolar disorder (BIP), while elevated IGP34, and IGP57 increased SCZ risk. High levels of IGP21 were associated with an increased risk of post-traumatic stress disorder (PTSD), while elevated levels of IGP22 exhibited a causal association with a decreased risk of attention-deficit/hyperactivity disorder (ADHD). No causal relationship between IgG N-glycan traits and autism spectrum disorder (ASD) and no evidence of reverse causal associations was found.ConclusionHere, we demonstrate that IgG N-glycan traits have a causal relationship with psychiatric disorders, especially IGP7’s protective role, offering new insights into their pathogenesis. Our findings suggest potential strategies for predicting and intervening in psychiatric disorder risk through IgG N-glycan traits.